Overexpression of GRK3, Promoting Tumor Proliferation, Is Predictive of Poor Prognosis in Colon Cancer - Jiang, Tao; Yang, Chun; Ma, Liyuan; Wu, Zehua; Ye, Ling; Ma, Xiaoqiang; Li, Hai; Fan, Junwei; Yang, Yinxue (Disease Markers, 2017)
Deregulation of G protein-coupled receptor kinase 3 (GRK3), which belongs to a subfamily of kinases called GRKs, acts as a promoter mechanism in some cancer types. Our study found that GRK3 was significantly overexpressed in 162 pairs of colon cancer tissues than in the matched noncancerous mucosa (P<0.01). Based on immunohistochemistry staining of TMAs, GRK3 was dramatically stained positive in primary colon cancer (130/180, 72.22%), whereas it was detected minimally or negative in paired normal mucosa specimens (50/180, 27.78%). Overexpression of GRK3 was closely correlated with AJCC stage (P=0.001), depth of tumor invasion (P<0.001), lymph node involvement (P=0.004), distant metastasis (P=0.016), and histologic differentiation (P=0.004). Overexpression of GRK3 is an independent prognostic indicator that correlates with poor survival in colon cancer patients. Consistent with this, downregulation of GRK3 exhibited decreased cell growth index, reduction in colony formation ability, elevated cell apoptosis rate, and impaired colon tumorigenicity in a xenograft model. Hence, a specific overexpression of GRK3 was observed in colon cancer, GRK3 potentially contributing to progression by mediating cancer cell proliferation and functions as a poor prognostic indicator in colon cancer and potentially represent a novel therapeutic target for the disease.